2012
DOI: 10.1038/clpt.2012.186
|View full text |Cite
|
Sign up to set email alerts
|

CYP2B6 and Bupropion’s Smoking-Cessation Pharmacology: The Role of Hydroxybupropion

Abstract: Bupropion is indicated to promote smoking cessation. Animal studies suggest that bupropion’s major metabolite hydroxybupropion can mediate bupropion’s pharmacologic activity. We measured plasma bupropion and metabolite levels in a double-blind, placebo controlled, randomized smoking cessation trial. Among the treatment adherent individuals, higher hydroxybupropion concentrations (per µg/mL) resulted in better smoking cessation outcomes (Week 3, 7 and 26 OR=2.82, 2.96 and 2.37, P=0.005–0.040), this was not obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(121 citation statements)
references
References 36 publications
5
113
0
3
Order By: Relevance
“…For example, plasma concentrations of varenicline could be measured in individuals prescribed this medication 34 to test for the effect of functional OCT2 alleles on medication plasma levels, to test association between medication plasma levels and prospective abstinence, and on the influence of the functional OCT2 alleles on prospective abstinence, as has been reported for the bupropion metabolite hydoxybupropion and CYP2B6 variation. 81 Effects of the functional OCT2 allele on brain structure and function may be observable, given prior studies that have identified effects on brain structure 82 and function 83 of cholinergic 47,84 and dopaminergic 40,85 alleles that influence smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, plasma concentrations of varenicline could be measured in individuals prescribed this medication 34 to test for the effect of functional OCT2 alleles on medication plasma levels, to test association between medication plasma levels and prospective abstinence, and on the influence of the functional OCT2 alleles on prospective abstinence, as has been reported for the bupropion metabolite hydoxybupropion and CYP2B6 variation. 81 Effects of the functional OCT2 allele on brain structure and function may be observable, given prior studies that have identified effects on brain structure 82 and function 83 of cholinergic 47,84 and dopaminergic 40,85 alleles that influence smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Among these metabolites, OH-BUP had the highest steady-state plasma levels, and has been shown to be pharmacologically active ( Fig. 1) (Damaj et al, 2004(Damaj et al, , 2010Zhu et al, 2012;Benowitz et al, 2013). Higher levels of OH-BUP, but not bupropion, were associated with greater rates of smoking cessation in smokers receiving bupropion treatment (Zhu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, an in vivo association between CYP2B6 genotype and OH-BUP levels and the ratio of OH-BUP to bupropion (OH-BUP/BUP ratio, an indicator of bupropion hydroxylation activity) has been shown. However, no associations between CYP2B6 genotype and the levels of the parent drug bupropion were observed (Kirchheiner et al, 2003;Zhu et al, 2012;Benowitz et al, 2013). Furthermore, when the potent CYP2B6 inhibitors clopidogrel and ticlopidine were given to healthy volunteers, their OH-BUP formation decreased dramatically (.80%), but there was little alteration in bupropion levels (Turpeinen et al, 2004(Turpeinen et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Çünkü bupropiyonun aktif metaboliti olan ve dopamin ve norepinefrin taşıyıcılarını inhibe eder hidroksibupropiyonda da azalmaya yol açar (26) . Yapılan bir çalışmada, yüksek hidroksibupriyon seviyesi olan bağımlıların sigara bırakma başarısının da daha yüksek olduğu göste-rilmiştir (27) . Ancak farklı çalışmalarda bu bulgu net olarak teyit edilememiştir (20) .…”
Section: Nikotin Bağımlılığına Yatkınlıkunclassified